2015
DOI: 10.2486/indhealth.2014-0182
|View full text |Cite
|
Sign up to set email alerts
|

2,5-hexanedione induced apoptosis in mesenchymal stem cells from rat bone marrow via mitochondria-dependent caspase-3 pathway

Abstract: 2,5-hexanedione (HD) induces apoptosis of nerve cells. However,the mechanism of HD-induced apoptosis remains unknown. Mesenchymal stem cells (MSCs) are multipotential stem cells with the ability to differentiate into various cell types. This study is designed to investigate the apoptosis induced by HD in rat bone marrow MSCs (BMSCs) and the related underlying mechanisms. The fifth generation of MSCs was treated with 0, 10, 20 and 40 mM HD respectively. The viability of BMSCs was observed by MTT. Apoptosis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…Isolation and expansion of BMSCs were performed as described previously 18 , 25) . Briefly, after rat euthanasia by cervical dislocation, BMSCs were harvested by repeated flushing of the femoral and tibial cavities and were cultured in low-glucose Dulbecco's Modified Eagle's Medium (L-DMEM; HyClone, Beijing, China) with 10% fetal bovine serum (NQBB, Hong Kong).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolation and expansion of BMSCs were performed as described previously 18 , 25) . Briefly, after rat euthanasia by cervical dislocation, BMSCs were harvested by repeated flushing of the femoral and tibial cavities and were cultured in low-glucose Dulbecco's Modified Eagle's Medium (L-DMEM; HyClone, Beijing, China) with 10% fetal bovine serum (NQBB, Hong Kong).…”
Section: Methodsmentioning
confidence: 99%
“…2,5-HD-induced oxidative damage has been demonstrated recently in rat tissues and organs, including nerves, ovary, uterus, liver, and kidney 15 - 17) . Our previous data have shown that 2,5-HD can induce apoptosis in the bone marrow mesenchymal stem cells (BMSCs) through a mitochondrial pathway 18) . Because excessive ROS are usually produced by uncoupling of the mitochondrial respiratory chain by the toxins 19) , we hypothesized that ROS play a role in the 2,5-HD-induced apoptosis in BMSCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The immunofluorescence double-staining method was used to ascertain the aggregated state of α-Syn in cells as previously described (Wang et al 2015). After fixation with 4% paraformaldehyde, the cell slides were rinsed in PBS and preincubated with 3% H 2 O 2 for 10 min and permeabilized with 0.3% Triton X-100 in PBS for 30 min.…”
Section: Immunofluorescence Double Staining For Aggregated α α α α-Symentioning
confidence: 99%
“…The Bcl-2 family comprises anti-apoptotic members (such as Bcl-2, and Bcl-XL) and pro-apoptotic proteins (such as Bax, Bak, and Bid) (Sadoul 1998). Among the identified caspases, caspase-3 is thought to be the key enzyme that induces apoptosis and is the ultimate enforcer of caspases in apoptosis (Chen et al 2015). The induced expression of A53T α-Syn in differentiated PC12 cells increased the intracellular ROS levels, which is accompanied by mitochondrial cytochrome C release and an elevation in caspase-9 and caspase-3 activities (Liu et al 2011).…”
Section: R a F T 18mentioning
confidence: 99%